1993
DOI: 10.1002/j.1552-4604.1993.tb01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Methylprednisolone Acetate (Medrol Tablets) for Seasonal Rhinitis: Examination of Dose and Symptom Response

Abstract: The authors compared the effect of several doses an oral corticosteroid on symptom profile and severity in ragweed hay fever. Thirty-one patients were randomized to receive 0, 6, 12, or 24 mg methylprednisolone (Medrol Tablets [MP], Upjohn, Kalamazoo, MI). A baseline week in which no treatment was given preceded the treatment comparison. At the end of this week, symptom diaries showed that most of the subjects were experiencing moderate or severe symptoms. The corticoid produced dose-related reduction in all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…This possibility certainly cannot be excluded, but it does not seem likely that this contributed significantly to the ultimate effect. The study used the same symptom score questionnaire, 4 which has often been used in clinical studies with good results.…”
Section: Effect Of Gencydomentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility certainly cannot be excluded, but it does not seem likely that this contributed significantly to the ultimate effect. The study used the same symptom score questionnaire, 4 which has often been used in clinical studies with good results.…”
Section: Effect Of Gencydomentioning
confidence: 99%
“…4 This questionnaire was completed each morning and evening, noting the following items: nasal (blocked nose, itchy nose, sneezing or a runny nose) and nonnasal symptoms (itchy/ burning eyes, watery eyes, redness around the eyes, itchy ears/ palate) on a 4-point scale (0 ϭ none, 1 ϭ mild, 2 ϭ strong, and 3 ϭ severe). Both total nasal score (TNS) and total nonnasal score (TNNS) could vary between 0 and 12.…”
Section: Instrumentsmentioning
confidence: 99%
“…In addition, evidence regarding a suitable dosage of this drug is lacking. Among oral GC, only methylprednisolone tablets are confirmed as an effective treatment for allergic rhinitis by a placebocontrolled trial; this trial showed that a daily dosage of 24 mg of methylprednisolone was necessary to obtain a significant improvement in all nasal symptoms [81]. Thus, the use of oral GC corresponding to 20-30 mg of prednisolone should be limited to a brief period of time (within 1 week) when treating patients with allergic rhinitis.…”
Section: Practical Guideline For Management Of Allergic Rhinitis In Jmentioning
confidence: 99%
“…The only controlled comparison between oral and injected steroids in rhinitis showed a therapeutic index in favour of the depot injection ( 118). Nevertheless, there are arguments in favour of oral administration ( 119). It is cheap, and the dosage can be adjusted to the changing need for treatment.…”
Section: Systemic Corticosteroidsmentioning
confidence: 99%